Expansion of B-1a Cells with Germline Heavy Chain Sequence in Lupus Mice - Holodick, Nichol E.; Zeumer, Leilani; Rothstein, Thomas L.; Morel, Laurence (Frontiers in Immunology, 2016)
B6.Sle1.Sle2.Sle3 (B6.TC) lupus-prone mice carrying the NZB allele of Cdkn2c, encoding for the cyclin-dependent kinase inhibitor P18INK4, accumulate B-1a cells due to a higher rate of proliferative self-renewal. However, it is unclear whether this affects primarily early appearing B-1a cells of fetal origin or later appearing B-1a cells that emerge from bone marrow. B-1a cells are the major source of natural autoantibodies, and it has been shown that their protective nature is associated with a germline-like sequence, which is characterized by few N-nucleotide insertions and a repertoire skewed towards rearrangements predominated during fetal life, VH11 and VH12. To determine the nature of B-1a cells expanded in B6.TC mice, we amplified immunoglobulin genes by PCR from single cells in mice. Sequencing showed a significantly higher proportion of B-1a cell antibodies display fewer N-additions in B6.TC mice than in B6 control mice. Following this lower number of N-insertions within the CDR-H3 region, the B6.TC B-1a cells display shorter CDR-H3 length than B6 B-1a cells. The absence of N-additions is a surrogate for fetal origin, as TdT expression starts after birth in mice. Therefore, our results suggest that the B-1a cell population is not only expanded in autoimmune B6.TC mice but also qualitatively different with the majority of cells from fetal origin. Accordingly, our sequencing results also demonstrated overuse of VH11 and VH12 in autoimmune B6.TC mice as compared to B6 controls. These results suggest that the development of lupus autoantibodies in these mice is coupled with skewing of the B-1a cell repertoire and possible retention of protective natural antibodies.